واقع صناعة المحتوى الإعلامي في ليبيا وتحدياته " دراسة استكشافية لعينة من صُناع محتوى الإعلام الرقمي" - صالح , سليمان رابح الشريف; الزبير, نزار محمد إبراهيم (Scientific Journal of University of Benghazi, 2022)
The purpose of this study was to explore the reality and challenges of media content creation in Libya. The qualitative approach was applied, by conducting in-depth semi-structured interviews with a purposive sample of digital media creators, in order to understand the phenomenon under investigation based on their point of view. The results of the study revealed that the Instagram and Facebook platforms were the most used by digital media content creators in Libya. Furthermore, the results showed that one of the reasons for the weakness of digital content creation in Libya because of the absence of support and encouragement, also the lack of economic competition which supports content creation, as well as the lack of seriousness of digital content creators in providing content with professional specifications.